Respuesta :

Answer:

1 1/6 - 7 3/6 = -19/

3

= -6 1/

3

≅ -6.3333333

Step-by-step explanation:

Conversion a mixed number 1 1/

6

to a improper fraction: 1 1/6 = 1 1/

6

= 1 · 6 + 1/

6

= 6 + 1/

6

= 7/

6

To find new numerator:

a) Multiply the whole number 1 by the denominator 6. Whole number 1 equally 1 * 6/

6

= 6/

6

b) Add the answer from previous step 6 to the numerator 1. New numerator is 6 + 1 = 7

c) Write a previous answer (new numerator 7) over the denominator 6.

One and one sixth is seven sixths

Conversion a mixed number 7 3/

6

to a improper fraction: 7 3/6 = 7 3/

6

= 7 · 6 + 3/

6

= 42 + 3/

6

= 45/

6

To find new numerator:

a) Multiply the whole number 7 by the denominator 6. Whole number 7 equally 7 * 6/

6

= 42/

6

b) Add the answer from previous step 42 to the numerator 3. New numerator is 42 + 3 = 45

c) Write a previous answer (new numerator 45) over the denominator 6.

Seven and three sixths is forty-five sixths

Subtract: 7/

6

- 45/

6

= 7 - 45/

6

= -38/

6

= 2 · -19/

2 · 3

= -19/

3

For adding, subtracting, and comparing fractions, it is suitable to adjust both fractions to a common (equal, identical) denominator. The common denominator you can calculate as the least common multiple of both denominators - LCM(6, 6) = 6. In practice, it is enough to find the common denominator (not necessarily the lowest) by multiplying the denominators: 6 × 6 = 36. In the next intermediate step, the fraction result cannot be further simplified by canceling.

In words - seven sixths minus forty-five sixths = minus nineteen thirds.